Estudo fitoquímico e investigação da atividade citotóxica do caule de Xylopia laevigata (Annonaceae) - Menezes, Leociley Rocha Alencar (2015)
Xylopia laevigata is a species of Annonaceae, popularly known as "meiu" and "pindaíba". It is an endemic tree of Brazil found in the states of Bahia, Paraíba, Piauí, Sergipe, Espírito Santo, Minas Gerais, Rio de Janeiro and São Paulo. The presente work describes the results obtained from the phytochemical studies bioguided from the stem of X. laevigata, front to the in vitro cytotoxic activity, which resulted in the isolation of 19 substances belonging to the class of alkaloids, which were elucidated on the basis of NMR analysis of 1H and 13C 1D/2D and MS as well as by comparison with the data of the literature. The isolated alkaloids were identified as: eleven alkaloids aporphine type, (R)-roemerine, (S)-anonaine, (S)-glaucine, (S)-xylopine, (S)-norglaucine, asimilobine, (S)-norpurpureine, (S)-N- methyllaurotetanine, (S)-norpredicentrine, (S)-calycinine and (S)-laurotetanine; two oxoaporphines: lanuginosine and oxoglaucine; four tetrahydroprotoberberine: (-)-xylopinine, (+) discretine, (-) corytenchine and (+)-discretamine; one benziltetrahydroisoquinoline: (+)- reticuline; and morphinandienone: (+)- flavinantine. The isolated alkaloids were described for the first time in the stem of X. laevigata, besides this is the first report of the isolation of an alkaloid of morphinandienone type (flavinantine) in the Xylopia genus. Of all the extracts and fractions, from the stem of X. laevigata, undergoing in vitro cytotoxic activity assay, the alkaloidal fraction from the methanol extract showed the highest activity against tumor cell lines evaluated with equal percentage inhibition of the 83.60 ± 1.32% and 89.48 ± 0.79% for HepG2 and HL60, respectively. Among the isolated alkaloids evaluated lanuginosine and xylopine showed the best results with strong activity against strains of K562 - human chronic myelocytic leukemia (IC50 = 6.61 μg mL-1 and 3.12 μg mL-1), HL-60 - human promyelocytic leukemia (IC50 = 7.81 μg mL-1 and 1.87 μg mL-1), HepG2 - human hepatocellular carcinoma (IC50 = 3.89 μgmL-1 and 1.87 μg mL-1) and B16-F10 - murine melanoma (IC50 = 8.46 μg mL- 1 and 3.77 μg mL-1), respectively, with IC50 values closest the positive control (doxorubicin). However, comparing with doxorubicin, lanuginosine showed a higher selectivity index for strain B16-F10. The results confirm that X. laevigata is chemically a native species of the family Annonaceae and a promising source of substances with potential cytotoxic activity.